(3YbdI GdEUHY (B((3KeHdjfG(B)s - (3GdSYOj, OfjGRGO,s 1973- ((3HjQhJs (3ghe CHdjO JQGjfjfZ,s, 2018)
(3JJdNU CSWhQI YbdI GdEUHY aj MWGH cGfJ RhLJg hdhOG fKhQG aJVY GdJhGFe eeG Vjb GdMGd Ydjg MjK UGQ dOjg SHYI ChdGO CcHQge aj GdYGTQI hCUZQge GdPj aj GdSGHYI Oeje VFjd ceG GdEUHY aSeGg GdCUjHY hQZe Cfg cGf CPci GdChdGO EdG Cfg CJYH hGdOjg gh hENhGfg ef bdI GdWYGe GdeJhaQ, aGJab GdhGdOGf djdG Ydi fHP GdChdGO aj GdZGHI MJi dG jTGgOhG YPGHge GdHWjA aj GdehJ ef GdLhY hSeYgeG GdCUjHY, aGMJGd ddCeQ hPgH aedC LjhHg HMUi GdTGWF hdeG Md Gddjd SGQ GdCHhGf HGdCWaGd aUGQ GdCUjHY jdbj GdMUi cd HVY NWhGJ djMaX NW GdYhOI HENhGfg Edi GdHjJ ef faS GdWQjb, adeG JQcge CHhGge aj GdZGHI Hci GdCWaGd aCScJge GdCUjHY hCYGOge Edi HjJ CHhjge eJJHYG Jdc GdMUi GdJj cGf jdbjgG aQLYh ddHjJ SGdejf, Ke aj GddjdI GdJGdjI CNPGge aLCI ade jLO GdCUjHY Shi cSQI GdNHR abWYgG aj GdWQjb aCcdJgG GdWjhQ hVd GdUZGQ SHjd GdYhOI, Ke UYO GdCUjHY TLQI aQCi fhQG eVGA cGf dHjJ GdZhd, aGSJbHdJge RhLI GdZhd aj ZQaI HfGJgG, adeG YGO GdZhd GTJe QGFMJge aCQGO Ccdge, aQLJg RhLJg Cf jfJXQ MJi GdUHGM hcPdc abO YQa GdCUjHY eG jLQj aCHOd bHYGJ ENhGfg aj Gddjd hge fGFehf LejYG HJjLGf HfGJ GdZhd, adeG gLe GdZhd aj Gddjd hbOGTJHgJ Ydjg GdQGFMI aCcd HfGJg hbO JSdd GdCUjHY HENhGfg gQHG aCOQc GdZhd eG aYd, adMbge HMPGFg Pj GdSHY aQGSN, aGdJLChG dcga UYH Ydjg ONhdg afGe ahbg, aGfSd GdCUjHY hSQb MPGAg aQGM Hg dRhLI GdZhd jNHQgG Cf GdZhd eMHhS YfO GddUhU hjWdHhfg GdaOjI hbO CQSd eY GdCUjHY GdMPGA dJJCcO, aCYWJge CehGd GdZhd, aYGO GdCUjHY HGdeGd eY ENhGfg dHjJ CHhjge hYGThG SYOGAs
(3GdbUU GdeJQLeIs
Keywords: (3COH GdCWaGds -- (3bQf (B21s -- (3JQLeGJ Edi GdYQHjIs; (3bUU GdCWaGds -- (3bQf (B21s -- (3JQLeGJ Edi GdYQHjIs